Challenges in Implementing Antimicrobial Stewardship Programmes at Secondary Level Hospitals in India: An Exploratory Study - Philip Mathew; Jaya Ranjalkar; Sujith John Chandy (Frontiers Media S.A., 2020)
Introduction: Implementing a sustainable and effective Antimicrobial Stewardship (AMS) programme in secondary level hospitals, in Low-Middle Income Country (LMIC) contexts, has numerous challenges. It is important to understand these challenges so that the stewardship initiatives can be tailored according to the unique requirements thrown up by these healthcare facilities. This study explores the experiences of implementing AMS in secondary level hospitals in the state of Kerala, India.Methods: A qualitative study was planned to map the challenges in implementing AMS in the secondary level hospitals. Toward the end of the 1 year followup period, the nodal officers at each hospital were interviewed using a semi-structured interview guide. The in-depth interviews were transcribed and later subjected to content analysis using N-Vivo 11.0, a popular software tool used for qualitative analysis.Results: Many physicians cite perceived patient satisfaction as one of the reasons for increased antibiotic use, as many patients consider antibiotics as standard of care. Also, the distance traveled by the patient and advancing age are factors which increase antibiotic use. The physician factors which determine use include empiric treatment needs, outbreak of diseases, absence of education programmes in antibiotic usage to fill in the knowledge gap and fear of litigation. The promotional activities by companies and antibiotics being a major source of income for small hospitals, affects use patterns. The factors which determine antibiotic selection includes conformism, experience of the physician, perceived resistance to certain antibiotics, emergence of specific diseases, and promotional activities related to antimicrobial agents. The challenges in implementing a sustainable stewardship programme is multifactorial. It includes competition between doctors, time constraints faced by physicians, absence of a champion, sub-optimal interdepartmental cooperation, absence of supporting facilities, dysfunctional regulatory systems, and unreliability of antibiograms.Discussion: AMS in resource-limited setting is going to be a challenge, especially in terms of financing, access to technologies and capacity building. Political and regulatory willpower of international partnerships should be effectively harnessed for designing solutions for LMIC contexts. Also, models for stewardship from elsewhere should undergo an adaptation process before implementation in low resource settings.